High Fertility is no Longer a Dividend: The Dynamics of a Big Young Population and Unemployment - Maghimbi, Sam (Tanzania Journal for Population studies and Development, 2019)
The problem of youth unemployment has been discussed many times in the current development debate. Pro-natalists like Professor Kamuzora have argued that a youth population is the ultimate resources for Africa for all time. The idea that the high rates of population growth (which lead to high population density) can be compatible with economic growth was advocated by Boserup. The paper considers the limitation of the assumed compatibility between high fertility and development in Tanzania. It is argued that the rapid increase of the many young people in the population is not compatible with their rapid upward social mobility. Youth unemployment is likely to remain a principle social economic problem for a long time because of high fertility. Some solutions to youth unemployment like vocational training and agricultural development are critically considered.